Complexes of Mn(II), Fe(III), Co(II), Ni(II) and Cu(II) with o-Hydroxyphenylurea - Sud, Dhiraj; Pannu, B.S. (Asian Journal of Chemistry, 2010)
The metal complexes of o-hydroxyphenylurea with composition LMnCl, L2FeCl, LCo(OH), LNiCl·H2O and LCuCl have been isolated and characterised with elemental analysis, conductance and infrared spectral data. All the complexes are non-ionic and polymers except LNiCl·H2O.